Humanoid Dynamic Controller - Rui Monteiro (2012)
In the last years several investigators have focused on the development and control of humanoid robots able to acquire human behaviors and features, in order to be able to interact with humans and work together with them. The fall of a umanoid robot can lead to damages, which entail costs for repair or even human health risks, so ensuring stability is a main concern in terms of cost and safety. This document presents the implementation of a dynamic controller for humanoid robots, able to position the robot's center of mass in a certain location operating as a stability module. It is also described a precise behavior of preparing an omnidirectional kick for a humanoid robot by placing the support foot in a precise position and orientation calculated in accordance with the robot's position, the ball and the target, and by transferring the robot's center of mass to the desired position.